In-Vitro Seed Germination and Effect of Growth Regulators on Subsequent Development of Protocorms of Eulophia Nuda Lindl - Dawande, Varsha; Gurav, Rajaram (International Journal of Applied Sciences and Biotechnology, 2015)
Asymbiotic seed germination of Eulophia nuda Lindl. was observed on Knudson C medium. About 90% seeds germinated within 8-10 weeks and formed green protocorms in 11-12 weeks. Effect of BA and IBA was studied on plantlet development from protocorms. BA shows the best results with respect to number and length of shoots. Maximum number (6.45±1.36) and length (3.90±0.99) was observed on MS medium supplemented with 4.44μM.BA. Maximum root growth was also observed on same medium (4.8±0.99 number of roots and 1.43±0.13cm length). The regenerated plantlets were successfully acclimatized and transferred to earthen pots. The results presented here show that in vitro seed germination and plantlet development in Eulophia nuda Lindl., an endangered orchid, can be achieved at a higher rate by this method. Int J Appl Sci Biotechnol, Vol 3(2): 243-247 DOI: http://dx.doi.org/10.3126/ijasbt.v3i2.12476